Koncepcje ustrojowe niemieckiej chadecji w latach 1945-1948. - Bożek, Michał (Wydawnictwo Poznańskie sp. z o.o., 2010)
A political formation for post-war Germany that would be based on the fundamental principles of Christian ethics was envisaged by German emigrants and the anti-Nazi movement already during the Second World War. The first Christian Democrat structures emerged immediately after the end of the war, in 1945, but initially they were nothing more than a conglomerate of many small parties which were only loosely related to one another. It therefore took some time before they developed into a largely uniform political party. The political system of the restored German state after the second world war was a widely discussed issue and one of the key programme items of the Christian Democrat party in the allied-occupied West Germany. Those discussions took place during the harmonisation process that was gradually taking place and encompassed different ideas stemming from different party fractions. From those emerged a model of the political system of the future state that was primarily intended to be a parliamentary democracy based on the rule of law, a federal type of state and one respecting the fundamental rights and freedoms of an individual, determined to join, on behalf of its citizens, the international community and be involved in the European integration process. Those general and widely supported goals marginalised the differences and alternative ideas emerging in the discussions of different Christian Democrat leaders. Undoubtedly, the issue of the overall political system of Germany was of primary importance in the first post-war years.
THE POLITICAL CONCEPT OF THE GERMAN CHRISTIAN DEMOCRATIC UNION BETWEEN 1945-1948.
Keywords: Niemcy; 1945-1948; Doktryny polityczne; Chadecja